25-((2+5y-3)(y+2))=-3(2y-5)-(5(y-1)-3y+3)

Simple and best practice solution for 25-((2+5y-3)(y+2))=-3(2y-5)-(5(y-1)-3y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25-((2+5y-3)(y+2))=-3(2y-5)-(5(y-1)-3y+3) equation:


Simplifying
25 + -1((2 + 5y + -3)(y + 2)) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)

Reorder the terms:
25 + -1((2 + -3 + 5y)(y + 2)) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)

Combine like terms: 2 + -3 = -1
25 + -1((-1 + 5y)(y + 2)) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)

Reorder the terms:
25 + -1((-1 + 5y)(2 + y)) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)

Multiply (-1 + 5y) * (2 + y)
25 + -1((-1(2 + y) + 5y * (2 + y))) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)
25 + -1(((2 * -1 + y * -1) + 5y * (2 + y))) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)
25 + -1(((-2 + -1y) + 5y * (2 + y))) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)
25 + -1((-2 + -1y + (2 * 5y + y * 5y))) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)
25 + -1((-2 + -1y + (10y + 5y2))) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)

Combine like terms: -1y + 10y = 9y
25 + -1((-2 + 9y + 5y2)) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)
25 + (-2 * -1 + 9y * -1 + 5y2 * -1) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)
25 + (2 + -9y + -5y2) = -3(2y + -5) + -1(5(y + -1) + -3y + 3)

Combine like terms: 25 + 2 = 27
27 + -9y + -5y2 = -3(2y + -5) + -1(5(y + -1) + -3y + 3)

Reorder the terms:
27 + -9y + -5y2 = -3(-5 + 2y) + -1(5(y + -1) + -3y + 3)
27 + -9y + -5y2 = (-5 * -3 + 2y * -3) + -1(5(y + -1) + -3y + 3)
27 + -9y + -5y2 = (15 + -6y) + -1(5(y + -1) + -3y + 3)

Reorder the terms:
27 + -9y + -5y2 = 15 + -6y + -1(5(-1 + y) + -3y + 3)
27 + -9y + -5y2 = 15 + -6y + -1((-1 * 5 + y * 5) + -3y + 3)
27 + -9y + -5y2 = 15 + -6y + -1((-5 + 5y) + -3y + 3)

Reorder the terms:
27 + -9y + -5y2 = 15 + -6y + -1(-5 + 3 + 5y + -3y)

Combine like terms: -5 + 3 = -2
27 + -9y + -5y2 = 15 + -6y + -1(-2 + 5y + -3y)

Combine like terms: 5y + -3y = 2y
27 + -9y + -5y2 = 15 + -6y + -1(-2 + 2y)
27 + -9y + -5y2 = 15 + -6y + (-2 * -1 + 2y * -1)
27 + -9y + -5y2 = 15 + -6y + (2 + -2y)

Reorder the terms:
27 + -9y + -5y2 = 15 + 2 + -6y + -2y

Combine like terms: 15 + 2 = 17
27 + -9y + -5y2 = 17 + -6y + -2y

Combine like terms: -6y + -2y = -8y
27 + -9y + -5y2 = 17 + -8y

Solving
27 + -9y + -5y2 = 17 + -8y

Solving for variable 'y'.

Reorder the terms:
27 + -17 + -9y + 8y + -5y2 = 17 + -8y + -17 + 8y

Combine like terms: 27 + -17 = 10
10 + -9y + 8y + -5y2 = 17 + -8y + -17 + 8y

Combine like terms: -9y + 8y = -1y
10 + -1y + -5y2 = 17 + -8y + -17 + 8y

Reorder the terms:
10 + -1y + -5y2 = 17 + -17 + -8y + 8y

Combine like terms: 17 + -17 = 0
10 + -1y + -5y2 = 0 + -8y + 8y
10 + -1y + -5y2 = -8y + 8y

Combine like terms: -8y + 8y = 0
10 + -1y + -5y2 = 0

Begin completing the square.  Divide all terms by
-5 the coefficient of the squared term: 

Divide each side by '-5'.
-2 + 0.2y + y2 = 0

Move the constant term to the right:

Add '2' to each side of the equation.
-2 + 0.2y + 2 + y2 = 0 + 2

Reorder the terms:
-2 + 2 + 0.2y + y2 = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 0.2y + y2 = 0 + 2
0.2y + y2 = 0 + 2

Combine like terms: 0 + 2 = 2
0.2y + y2 = 2

The y term is 0.2y.  Take half its coefficient (0.1).
Square it (0.01) and add it to both sides.

Add '0.01' to each side of the equation.
0.2y + 0.01 + y2 = 2 + 0.01

Reorder the terms:
0.01 + 0.2y + y2 = 2 + 0.01

Combine like terms: 2 + 0.01 = 2.01
0.01 + 0.2y + y2 = 2.01

Factor a perfect square on the left side:
(y + 0.1)(y + 0.1) = 2.01

Calculate the square root of the right side: 1.417744688

Break this problem into two subproblems by setting 
(y + 0.1) equal to 1.417744688 and -1.417744688.

Subproblem 1

y + 0.1 = 1.417744688 Simplifying y + 0.1 = 1.417744688 Reorder the terms: 0.1 + y = 1.417744688 Solving 0.1 + y = 1.417744688 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.1' to each side of the equation. 0.1 + -0.1 + y = 1.417744688 + -0.1 Combine like terms: 0.1 + -0.1 = 0.0 0.0 + y = 1.417744688 + -0.1 y = 1.417744688 + -0.1 Combine like terms: 1.417744688 + -0.1 = 1.317744688 y = 1.317744688 Simplifying y = 1.317744688

Subproblem 2

y + 0.1 = -1.417744688 Simplifying y + 0.1 = -1.417744688 Reorder the terms: 0.1 + y = -1.417744688 Solving 0.1 + y = -1.417744688 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-0.1' to each side of the equation. 0.1 + -0.1 + y = -1.417744688 + -0.1 Combine like terms: 0.1 + -0.1 = 0.0 0.0 + y = -1.417744688 + -0.1 y = -1.417744688 + -0.1 Combine like terms: -1.417744688 + -0.1 = -1.517744688 y = -1.517744688 Simplifying y = -1.517744688

Solution

The solution to the problem is based on the solutions from the subproblems. y = {1.317744688, -1.517744688}

See similar equations:

| 5v+7v=-32 | | 5z-4=-7 | | -5x-6(4x+10)=114 | | 1=1w+37 | | (5y+9)-(8y-5)= | | c=40+2n | | 3x-15+6x+22=45 | | 6.1=7.9-0.3x | | c=2n+40 | | -1=1w+37 | | (2x+5)+(2x+4)=(2x) | | 2c(4)=11c-33 | | 9t+16=-2 | | -3x-5(x+18)=-26 | | 2+8y=8+5y | | (5-y)+(16-y)-(5-y)=0 | | 1/5=3p+4 | | 5(3e+5)-25e=0 | | 1v+1=20 | | 1/5=3p | | -3.1b+2.1=-0.7(5b-6) | | -247=-8(1+5n)+1 | | 3x(x-2)+4=2x-1 | | -27=-7x+2(7x+11) | | 7(7x+1)-4x=13(3c-2) | | 1200+750=9500 | | 0.06(y-0.5)=0.06y+0.09 | | 17x^2+1=2x | | 70=5b+10 | | -6x+4(2x-15)=-50 | | (k-1)=3x^2+3x+2 | | .25(x+.4)=.1x-1.6 |

Equations solver categories